High-speed rail accessibility and haze pollution in China: A spatial econometrics perspective. (May 2021) - Zhang, Fan; Wang, Feng; Yao, Shujie
Highlights: One standard deviation increases in HSR accessibility reduce the PM2.5 concentration by 0.22%. Effects of HSR on haze pollution varies among different city classifications. HSR reduce haze pollution by improving the efficiency of resource allocation. HSR reduce haze pollution by promoting industrial structure change. HSR reduce haze pollution by technological innovation. Abstract: With deteriorating air quality in Chinese cities, high-speed rail (HSR) has attracted serious attention as an efficient transportation system to contain haze pollution across the country. This study introduces the concept of HSR accessibility and applies the generalized spatial two-stage least square method to examine the effect of HSR on haze pollution in China. A time-varying difference-in-difference strategy is then employed to recognize the causality from HSR to the haze pollution and eliminate endogeneity. Based on a panel dataset comprising 285 cities over 2010–2018, we find a negative effect of HSR accessibility on haze pollution. An increase of one standard deviation in HSR accessibility reduces PM2.5 concentration by 0.22%. However, the HSR pollution reduction effect varies significantly across cities. It is found that HSR can reduce haze pollution by improving the efficiency of resource allocation as well as promoting industrial structure change and technological innovation. This study proposes a new solution for pollution, i.e., improving urbanization quality through intercity transport efficiency enhancement.